2013
DOI: 10.1038/srep02439
|View full text |Cite
|
Sign up to set email alerts
|

Exploring electronic structure of one-atom thick polycrystalline graphene films: A nano angle resolved photoemission study

Abstract: The ability to produce large, continuous and defect free films of graphene is presently a major challenge for multiple applications. Even though the scalability of graphene films is closely associated to a manifest polycrystalline character, only a few numbers of experiments have explored so far the electronic structure down to single graphene grains. Here we report a high resolution angle and lateral resolved photoelectron spectroscopy (nano-ARPES) study of one-atom thick graphene films on thin copper foils s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
89
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 47 publications
18
89
1
Order By: Relevance
“…We checked that the physics of the graphene low energy states does not change upon increasing the number of layers. In addition, we found good agreement of the band structure with experiment [8][9][10][11][12][13][14].…”
Section: A Choice Of Unit Cellsupporting
confidence: 66%
See 3 more Smart Citations
“…We checked that the physics of the graphene low energy states does not change upon increasing the number of layers. In addition, we found good agreement of the band structure with experiment [8][9][10][11][12][13][14].…”
Section: A Choice Of Unit Cellsupporting
confidence: 66%
“…STM experiments [4] observe regions with different moiré structures; the most observed one (30%) is a commensurate lattice configuration with a periodicity of 66Å. Another experiment [8] found that 60% of graphene grains on Cu(111) are preferentially rotated by 3…”
Section: A Choice Of Unit Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Angle Resolved Photoelectron Spectroscopy experiments (ARPES) were performed at beamline I4, which covers the energy range 14 to 160 eV. Microand nano-ARPES experiments were carried out at the ANTARES beamline [83,84] at the SOLEIL laboratory in France. This instrument allowed ARPES spectra to be collected from selected micro-or nano-sized areas on the surface, compared to the almost mm-sized probing area obtained at beamline I4.…”
Section: Photoelectron Spectroscopy (Pes)mentioning
confidence: 99%